2008
DOI: 10.1007/s00005-008-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

Opiate abuse, innate immunity, and bacterial infectious diseases

Abstract: The first line of defense against invading bacteria is provided by the innate immune system. Morphine and other opiates can immediately disrupt the body's first line of defense against harmful external bacteria. Opiate, for example morphine, abuse degrades physical and physiologic barriers, and modulates phagocytic cells (macrophages, neutrophils) and, nonspecific cytotoxic T cells (gammadelta T), natural killer cells, and dendritic cells, that are functionally important for carrying out a rapid immune reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 82 publications
1
46
0
Order By: Relevance
“…Indeed, morphine and its derivatives interact with the mu receptor expressed on various immune cell types including lymphocytes and NK cells. Multiple in vitro and in vivo experiments have demonstrated that it can suppress production of cytokines and proliferation of lymphocytes and inhibit NK cell activity in humans, monkey and rodents [39][40][41]. Drug abuse in our cohort of HCV-exposed IDUs could account for low IFN-γ production during baseline.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Indeed, morphine and its derivatives interact with the mu receptor expressed on various immune cell types including lymphocytes and NK cells. Multiple in vitro and in vivo experiments have demonstrated that it can suppress production of cytokines and proliferation of lymphocytes and inhibit NK cell activity in humans, monkey and rodents [39][40][41]. Drug abuse in our cohort of HCV-exposed IDUs could account for low IFN-γ production during baseline.…”
Section: Discussionmentioning
confidence: 83%
“…This probably reflects a shut-off mechanism to guard against liver inflammation and the development of immune suppressive IL-10 NK cells. Alternatively, it was demonstrated that HCV infected hepatocytes express enhanced levels of HLA-E and that the HLA-A2 restricted epitope HCV core AA (35)(36)(37)(38)(39)(40)(41)(42)(43)(44) stabilizes HLA-E expression [18]. Since NKG2A binds to HLA-E, enhanced expression of NKG2A by NK cells from chronic HCV patients resulted in reduced cytolysis of HLA-E expressing hepatocytes [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that opiate abuse causes immunosuppression by disrupting both innate and adaptive components of the immune system (26,33). Opiate abuse is a critical risk factor for increasing susceptibility and severity of bacterial infection, including S. pneumoniae (31,32).…”
mentioning
confidence: 99%
“…Opioid use and abuse renders individuals susceptible to infection (see Eisenstein et al, 2006;Wang et al, 2008) and a variety of mechanisms have been proposed to explain how opioids suppress the immune system. These mechanisms include effects on both the innate and adaptive branches of the immune system.…”
Section: Introductionmentioning
confidence: 99%